Development of an assay for in vivo human neutrophil elastase activity. Increased elastase activity in patients with alpha 1-proteinase inhibitor deficiency. - Weitz, J I (1986)
Leukocyte extracts contain enzymes that digest fibrinogen and release a fibrinopeptide A-containing fragment. This study was undertaken to identify the responsible proteinase and to characterize the fibrinopeptide A-containing fragment so that it could be used as an index of enzyme activity. Both the fibrinogenolytic activity and the release of the fibrinopeptide A-containing fragment mediated by the leukocyte extracts were shown to be due to human neutrophil elastase (HNE) by the following criteria: activity was completely blocked by a specific HNE inhibitor or by adsorbing HNE from the extracts with a monospecific antibody and reconstitution with purified HNE restored the ability to release the fibrinopeptide A-containing fragment. This fragment was not released by a variety of other proteinases or by HNE-inhibitor complexes indicating that, at least with respect to the enzymes tested, it is a specific product of HNE and its release requires the free enzyme. By separating the products of HNE digestion of fibrinogen using high performance liquid chromatography, identifying the immunoreactive fractions and subjecting them to amino acid analysis, the fragment was identified as A alpha 1-21, indicating an HNE cleavage site at the Val(A alpha 21)-Glu(A alpha 22) bond. The mean plasma A alpha 1-21 level was markedly higher in patients with alpha 1-proteinase inhibitor deficiency as compared to healthy controls (0.2 nM vs. 7.9 nM; P less than 0.0001), consistent with increased in vivo HNE activity in these individuals.